2017
DOI: 10.1177/2150135116683939
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Retraining and Double Switch in Patients With Congenitally Corrected Transposition of the Great Arteries

Abstract: The data demonstrate that LV retraining has been highly effective in this select group of patients with CC-TGA. The data also demonstrate that the results of the double-switch procedure have been excellent at midterm follow-up. These results suggest that LV retraining and double switch offer a reliable strategy option for patients with CC-TGA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 40 publications
(52 reference statements)
0
26
0
Order By: Relevance
“…Based on previous experience derived from re-training of the subpulmonary left ventricle before anatomical correction in congenitally corrected transposition of the great arteries (TGA) or before arterial switch for dextro-TGA (D-TGA), (22)(23)(24)(25) PAB has been applied to treat ESHF in children with DCM and preserved right ventricle function (26).…”
Section: Pulmonary Artery Banding For Myocardial Rehabilitationmentioning
confidence: 99%
“…Based on previous experience derived from re-training of the subpulmonary left ventricle before anatomical correction in congenitally corrected transposition of the great arteries (TGA) or before arterial switch for dextro-TGA (D-TGA), (22)(23)(24)(25) PAB has been applied to treat ESHF in children with DCM and preserved right ventricle function (26).…”
Section: Pulmonary Artery Banding For Myocardial Rehabilitationmentioning
confidence: 99%
“…Since then, numerous centers have reported favorable outcomes following anatomic repair. 12 18 When considering the strategy of anatomic correction, the incomplete natural history data on the systemic RV in this condition confounds the decision to routinely proceed with anatomic correction (with or without LV training) at the time of diagnosis, even during childhood, particularly in the absence of signs or symptoms of RV or Tricuspid value (TV) dysfunction. For purposes of management strategy, three basic decision points might be considered at the time of presentation: No or minor associated cardiac lesions that don’t require surgical intervention with preserved RV function; Major associated cardiac lesions that merit operation with preserved RV function; The development of major RV dysfunction at any time, but without symptoms; and The development of major RV dysfunction with heart failure symptoms. …”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary artery banding and anatomic correction before two and three years of age have been recommended to allow for ventricular hyperplasia instead of hypertrophy, theoretically reducing the chances of left ventricular failure. 13,15…”
Section: Natural History and Recommendations After Rv Dysfunction Devmentioning
confidence: 99%
“…Anatomic correction for ccTGA, which is known as a double switch operation, is expected to improve long-term outcomes by utilizing the mLV as a systemic pumping chamber. 1 Hraska et al reported that the survival and freedom from any event after a double switch operation were 95% and 71%, respectively, at 15-year follow-up. 2 Pulmonary artery banding is performed for mLV training before the double switch operation when the pressure of mLV is low.…”
Section: Discussionmentioning
confidence: 99%
“…An atrial–arterial switch (double switch) operation has been shown to improve patient survival. 1 A pulmonary artery banding (PAB) is performed for morphological left ventricle (mLV) training before a double switch operation when the mLV pressure is low. Pulmonary artery banding has also been reported to result in ventricular septal movement, improvement in tricuspid valve coaptation, and decrease in tricuspid valve regurgitation (TR).…”
Section: Introductionmentioning
confidence: 99%